(untitled) (Research, Society and Development, 2021)
Notification forms are important documents as they contain information that composes epidemiological and statistical data responsible for indicators of health, prevention and disease control. Dengue and Chikungunya have generated great concerns in relation to public health worldwide, which reinforces and highlights the importance of health education actions about these diseases. The objective of this study is to analyze the data quality of the Compulsory Notification Forms for Dengue and Chikungunya, aiming to present strategies for actions in Permanent Health Education (EPS). The research method was chosen through quantitative and documentary study. Data collection was carried out on 1,934 Individual Notification Forms (FNI), Notification/Conclusion Forms and Investigation Forms for Dengue and Chikungunya Fever, which were filled in from January 1st to December 31st, 2019 in a municipality of the metropolitan region of Rio de Janeiro. The most reported disease was Chikungunya, present in 77.5% of the notifications, and the main notifying professional is the Nurse, responsible for 43.1% of the records. Only 0.8% of the notification forms are filled out completely correctly and, of the 71 variables surveyed, 29 showed failures in filling out. The percentage of duplicate records is 12.1%. The need for interventions to improve the quality of notifications is real and evident, as well as the creation of strategies in EPS, to raise awareness, encourage and provide structure for professionals to perform the notification with greater richness and quality of data.